The time is right to implement Enhanced Recovery After Surgery (ERAS) broadly across pediatric surgery - Gregg Nelson (Elsevier, 2024)
ERAS is a global surgical quality improvement program that has demonstrated benefit across numerous surgical disciplines in terms of both clinical outcome improvements for patients and cost savings for the healthcare system. Successful implementation of ERAS is contingent on a well-functioning multidisciplinary team that uses audit to iterate towards increased ERAS protocol compliance. Although pediatric surgery was slow initially to adopt ERAS, there have been several important developments over the last 5 years including publication of the first ERAS® Society guideline in neonatal intestinal surgery and formation of the Pediatric ERAS® Society. The time is right to implement ERAS broadly across pediatric surgery.